(untitled) - Sonis, Stephen T. (Philadelphia, Pa., 2003)
Written in question-and-answer format, this guide provides information on the dental care of medically compromised patients, with advice on managing the various conditions affecting the mouth. Eighteen chapters by doctors associate with Harvard and Yale address the various types of disease, discuss patient assessment, and describe cases. B&w images accompany the case descriptions. An extensive bibliography lists other resources by disease type.
Keywords: Oral medicine,Mouth,Bệnh lý miệng,Nha khoa; Diseases